Risk and protective factors associated with gastrointestinal parasites in dogs from an urban area of Córdoba, Argentina. - Motta, Carlos Eugenio (2019)
Prevalence of gastrointestinal (GI) parasites and the effect of associated factors were evaluated in household dogs from an urban area of Córdoba, Argentina. A total of fecal samples were collected during 2010 and 2013, and processed with Willis´ salt, Sheaters´ sugar flotation and formol-ether concentration techniques. Overall prevalence of GI parasites was 45.23% (95% C.I.: 40.83; 49.62), Ancylostoma caninum (30.83%) was the most frequent parasite, followed by Trichuris vulpis (9.94%), Cystoisospora spp. (7.71%), Toxocara canis (6.90%) and Giardia spp. (5.88%). Independent variables werepresence of at least one parasite element, named all parasites, and GI parasites more frequently present as separate outcomes. Logistic regression results showed an increased risk related to age (P = 0.0343)for all parasites and for T. canis, Cystoisospora spp. and Giardia spp. Statistically significant and protective variables were no ingestion of small animals, daily feces removal and absence of shadow in house yards. Use of anthelmintics and daily feces removal for A. caninum, female gender and absence of shadow for T. canis resulted in protective factors. Effective actions for prevention, control and treatment are required in the research area, being the role played by veterinarians and owners commitment key aspects.